2022
DOI: 10.30541/v40i2pp.107-114
|View full text |Cite
|
Sign up to set email alerts
|

The Stock Market and the Economy in Pakistan

Abstract: This paper re-examines the causal relationship between stock prices and macro variables like consumption expenditure, investment spending, and economic activity (measured by GDP) in Pakistan. Using annual data from 1959-60 to 1998-99 and applying cointegration and error correction analysis, the paper indicates the presence of long-run relationship between stock prices and macro variables. Regarding the cause and effect relationship, the analysis indicates a one-way causation from macro variables to stock price… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 4 publications
0
20
0
Order By: Relevance
“…They concluded that crisis was due to poor policy formulation on the part of the policy maker as they lacked both credibility and transparency. Husain & Mahmood (2001) used the cointegration and the error correction analysis to examine the relationship between the stock prices and the macro variables, namely consumption expenditure, investment spending and GDP. They found that there exist a long-term relationship between stock prices and the macro variables.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They concluded that crisis was due to poor policy formulation on the part of the policy maker as they lacked both credibility and transparency. Husain & Mahmood (2001) used the cointegration and the error correction analysis to examine the relationship between the stock prices and the macro variables, namely consumption expenditure, investment spending and GDP. They found that there exist a long-term relationship between stock prices and the macro variables.…”
Section: Literature Reviewmentioning
confidence: 99%
“…consumption, investment, gross domestic product, index of industrial production). For example, Husain and Mahmood (2001) indicated one-way causation from macroeconomic variables to stock prices. Nishat and Shaheen (2004) reported that bidirectional causality exists between industrial production and stock prices.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The Method section describes in detail how the study was conducted, including conceptual and operational definitions of the variables used in the study, Different types of studies will rely on different methodologies; One of the previous studies conducted by Husain and Mahmood (2001) investigated the causal relationship between the stock market and economic growth in Pakistan. Farooq, Keung, and Kazmi (2004) conducted research to find out the existence of the causal relationship between the stock exchange prices and Exchange rate in Pakistan, and for this analysis, the stock market prices were taken from KSE.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study investigated long run relationship as well as causality between selected macroeconomic indicators and stock prices at LSE. Husain and Mahmood (2001) A study conducted by Kim (2003) suggested that stock returns in U.S are positively associated with the industrial production but is negatively related to the exchange rate, interest rate, and inflation in the long run. Gan, Lee, Yong, and Zhang (2006) found that macroeconomic variables interest rate, money supply, and real GDP does Granger cause stock returns in New Zealand and the stock market in New Zealand is not a leading indicator for changes in selected macroeconomic variables in the study.…”
Section: Literature Reviewmentioning
confidence: 99%